A dynamic stakeholder model: An Other‐oriented ethical approach. (6th February 2019) - Hatami, Akram; Firoozi, Naser
Abstract: In this paper, we reflect on the role of the Other in ethical decision‐making in corporations. The Other, in the form of a corporation's stakeholders, has already been discussed in the scientific literature, but there are still some Others that remain unconsidered and that call on corporations to be responsible. Drawing on the philosophy of Levinas, we wish to highlight a green earth and future generations as two non‐immediate Others within a corporation's group of stakeholders whose voices are silenced. We argue that Levinasian ethics can be used as a framework to extend traditional stakeholder theory in a dynamic sphere. With this model, corporations can understand the vital role that both a green earth and future generations play in their existence and can respond to contingencies by considering delays. We enrich our paper with illustrative cases to present some serious environmental disasters that have occurred as a result of ignoring the Other. Finally, we show that understanding the Other as a part of a corporation's identity can create new avenues for "infinite responsibility" towards Others. We contribute to the relevant literature by highlighting that both a green earth and future generations are important but ignored stakeholder parties whose claims urgently need to be addressed.